Loss of Foxd4 Impacts Neurulation and Cranial Neural Crest Specification During Early Head Development - McMahon, Riley; Sibbritt, Tennille; Aryamanesh, Nadar; Masamsetti, V. Pragathi; Tam, Patrick P. L. (Frontiers in Cell and Developmental Biology, 2022)
The specification of anterior head tissue in the late gastrulation mouse embryo relies on signaling cues from the visceral endoderm and anterior mesendoderm (AME). Genetic loss-of-function studies have pinpointed a critical requirement of LIM homeobox 1 (LHX1) transcription factor in these tissues for the formation of the embryonic head. Transcriptome analysis of embryos with gain-of-function LHX1 activity identified the forkhead box gene, Foxd4, as one downstream target of LHX1 in late-gastrulation E7.75 embryos. Our analysis of single-cell RNA-seq data show Foxd4 is co-expressed with Lhx1 and Foxa2 in the anterior midline tissue of E7.75 mouse embryos, and in the anterior neuroectoderm (ANE) at E8.25 alongside head organizer genes Otx2 and Hesx1. To study the role of Foxd4 during early development we used CRISPR-Cas9 gene editing in mouse embryonic stem cells (mESCs) to generate bi-allelic frameshift mutations in the coding sequence of Foxd4. In an in vitro model of the anterior neural tissues derived from Foxd4-loss of function (LOF) mESCs and extraembryonic endoderm cells, expression of head organizer genes as well as Zic1 and Zic2 was reduced, pointing to a need for FOXD4 in regulating early neuroectoderm development. Mid-gestation mouse chimeras harbouring Foxd4-LOF mESCs displayed craniofacial malformations and neural tube closure defects. Furthermore, our in vitro data showed a loss of FOXD4 impacts the expression of cranial neural crest markers Twist1 and Sox9. Our findings have demonstrated that FOXD4 is essential in the AME and later in the ANE for rostral neural tube closure and neural crest specification during head development.